Let's simplify the expression \((2^{-3} \cdot 9^3)^{-4}\) over \(2^9 \cdot 9^{-10}\) step by step while ensuring we end up with only positive exponents.
-
Start with the numerator: \[ (2^{-3} \cdot 9^3)^{-4} = 2^{-3 \cdot -4} \cdot 9^{3 \cdot -4} = 2^{12} \cdot 9^{-12} \]
-
The denominator remains: \[ 2^9 \cdot 9^{-10} \]
-
Now combine the numerator and denominator: \[ \frac{2^{12} \cdot 9^{-12}}{2^9 \cdot 9^{-10}} = \frac{2^{12}}{2^9} \cdot \frac{9^{-12}}{9^{-10}} \]
-
Apply the properties of exponents:
- For the base \(2\): \[ \frac{2^{12}}{2^9} = 2^{12 - 9} = 2^3 \]
- For the base \(9\): \[ \frac{9^{-12}}{9^{-10}} = 9^{-12 - (-10)} = 9^{-12 + 10} = 9^{-2} \]
-
Therefore, we have: \[ 2^3 \cdot 9^{-2} = \frac{2^3}{9^2} \]
Since the prompt requests an expression with only positive exponents, the equivalent expression is: \[ \frac{2^3}{9^2} \]
Thus, the correct response is: 2 to the power of 3 over 9 to the power of 2 (Start Fraction 2 cubed over 9 squared end fraction).